Inflammatory and vascular biomarkers in post-COVID-19 syndrome: A systematic review and meta-analysis of over 20 biomarkers - Yong, Shin Jie *; Halim, Alice; Halim, Michael; Liu, Shiliang; Aljeldah, Mohammed; Shammari, Basim R Al; Alwarthan, Sara; Alhajri, Mashael; Alawfi, Abdulsalam; Alshengeti, Amer; Khamis, Faryal; Alsalman, Jameela; et al. (Wiley, 2023)
Severe acute respiratory syndrome coronavirus 2 may inflict a post-viral condition known as post-COVID-19 syndrome (PCS) or long-COVID. Studies measuring levels of inflammatory and vascular biomarkers in blood, serum, or plasma of COVID-19 survivors with PCS versus non-PCS controls have produced mixed findings. Our review sought to meta-analyse those studies. A systematic literature search was performed across five databases until 25 June 2022, with an updated search on 1 November 2022. Data analyses were performed with Review Manager and R Studio statistical software. Twenty-four biomarkers from 23 studies were meta-analysed. Higher levels of C-reactive protein (Standardized mean difference (SMD) = 0.20; 95% CI: 0.02-0.39), D-dimer (SMD = 0.27; 95% CI: 0.09-0.46), lactate dehydrogenase (SMD = 0.30; 95% CI: 0.05-0.54), and leukocytes (SMD = 0.34; 95% CI: 0.02-0.66) were found in COVID-19 survivors with PCS than in those without PCS. After sensitivity analyses, lymphocytes (SMD = 0.30; 95% CI: 0.12-0.48) and interleukin-6 (SMD = 0.30; 95% CI: 0.12-0.49) were also significantly higher in PCS than non-PCS cases. No significant differences were noted in the remaining biomarkers investigated (e.g., ferritin, platelets, troponin, and fibrinogen). Subgroup analyses suggested the biomarker changes were mainly driven by PCS cases diagnosed via manifestation of organ abnormalities rather than symptomatic persistence, as well as PCS cases with duration of <6 than ≥6 months. In conclusion, our review pinpointed certain inflammatory and vascular biomarkers associated with PCS, which may shed light on potential new approaches to understanding, diagnosing, and treating PCS.